HUBUNGAN LINGKUNGAN BELAJAR TERHADAP KONSENTRASI BELAJAR SISWA SMP NEGERI 9 PADANGSIDIMPUAN DI KELAS VIII - Ramita Putri; Eni Sumanti Nasution; Evitamala Siregar (Universitas Gara Nusantara Padangsidimpuan, 2026)
This study aims to determine the relationship between the learning environment and student learning concentration. This study uses quantitative correlational methods. This study was conducted at SMP Country 9 Padangsidimpuan with a sample of 27 students. This study used correlational analysis and simple linear regression. Sampling was taken using a purposive sampling method. The data instrument used was a questionnaire. According to (Sugiono, 2018), a questionnaire is a data collection technique by providing written questions to respondents to answer. There are two variables in this study: the learning environment variable (X) and the learning concentration variable (Y). Based on the data obtained using SPSS 23 software, it was found that the significance of both variables, namely the learning environment questionnaire and the learning concentration questionnaire, was 0.07, which means it is smaller than 0.05, which means there is a relationship between the learning environment and the learning concentration of students at SMP Country 9 Padangsidimpuan.